IMPLEMENTASI STRATEGI PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) AMERTA JYOTI DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DESA (PADES) DI DESA BERABAN, KECAMATAN KEDIRI, KABUPATEN TABANAN - Ni Luh Pinky Novi Yani; I Wayan Mirta; I Gusti Agung Ayu Yuliartika Dewi (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2024)
The Village-Owned Enterprise (BUMDes) is a business entity aimed at managing economic ventures and public services to increase village income and empower the community. Based on Law Number 6 of 2014 and Government Regulation Number 11 of 2021, BUMDes is a legal entity established to manage the potential of the village, increase village original income, and develop village resources. The Amerta Jyoti Village-Owned Enterprise is a legal entity established by Beraban Village to manage businesses, utilize village assets, develop investments and productivity, and provide public services supported by work programs and the implementation of strategies owned by BUMDes. However, in relation to the implementation of the BUMDes strategy, it has not been carried out optimally. This can be seen from the unstable income of BUMDes each year, which means that its contribution to the original income of Beraban Village is still not optimal. Therefore, this research aims to determine the implementation of the strategy of managing BUMDes Amerta Jyoti in Beraban Village in efforts to increase village original income. The method used in this research is descriptive qualitative. The data collection techniques used include observation, interviews, and documentation. The data sources of this research come from primary and secondary data. The technique for determining informants in this research is purposive sampling, where selection is made based on certain considerations. The informants in this research consisted of 6 people based on their roles, fields, and understanding. The data analysis technique used includes data collection, data presentation, conclusion drawing, and data reduction. The analysis used is one of the strategic management approaches according to Wheelen and Hunger, which is strategy implementation with indicators used to analyze in this study, such as programs, budgets, and procedures. The results of this study show that the implementation of the strategy of BUMDes Amerta Jyoti in Beraban Village to increase village original income has not been maximized. This can be seen from the programs that have not been optimally implemented due to the need for more effective strategy application, the budget that requires strengthening of capital, both from the village government or from BUMDes income, and the procedures that have been carried out according to applicable policies.